The ancient past and fiction, or about the construction of worlds by humanities scholars: A review of books - D.E. Martynov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper reviews three novels by different modern authors, all published in 2020 and applying to the realities of Ancient Rome. Marik Lerner’s science fiction novel “Practical Ufology” fits within the subliterary genre of “accidental travel”, and any background information from the Roman-Byzantine life is not very appropriate in the adventure text. The new novel “The Triumphant” by Olga Eliseeva, a professional historian, can be labeled as a form of the “science novel” genre, because it has numerous references and “anchors” that only an educated person is able to understand. The main canvas of O. Eliseeva’s novel is a synthesis of the personalities and actions of Julius Caesar and Constantine the Great, so the writer used the motif of the fantasy world, in which the Roman Republic and Rome are replaced by Latium and Eternal City with the Nazarenes (i.e., Christians) playing an important role in its future. The trilogy “Divine World” by Boris Tolchinsky, a professional politologist, is the most radical inversion of the reality with its own alternative history. The world of the Amorian Empire is a synthesis of the ancient Mediterranean and the ancient Egyptian civilizations. These texts can be considered as “imperial literature” tied to the post-Soviet realities and projects aimed to find a better future.